STATE DOMINATION ENFORCEMENT IN TENNIS IN NABLUS (2015) BY ISMAIL KHALIDI - Herry Sutama; Desvalini Anwar (Universitas Negeri Padang, 2019)
The purpose of this analysis is to expose the issue of State domination enforcement. It is also intended to find out how the characters, setting, plot or conflict to contribute in revealing the issue of State domination enforcement. This analysis is related to the concept of Power/Knowledge by Michel Foucault and Orientalism by Edward Said that is supported by the text and context based interpretation. The result of this analysis shows that the State that is represented by British enforces the domination through law enforcement and media restriction.